Effects Of Measurement Conditions On Pressure-Concentration Isotherm And Thermodynamic Properties Of Lani4.6al0.4 Hydride. (2018) - Sharma, Vinod Kumar; Mohan, Man; Badiganti, Chandra Mouli
Abstract: Pressure-concentration isotherms (PCIs) of LaNi4.6 Al0.4 metal hydride are measured using a Sievert's Apparatus at different temperatures to study the phenomenon of the formation of metal hydrides. PCI properties (plateau pressures, plateau slope, hysteresis, etc.) and thermodynamic properties (reaction enthalpy and entropy) of LaNi4.6 Al0.4 metal hydride are calculated. To understand the effects of measurement parameters on PCI and thermodynamic properties the experimental conditions are varied. During the PCI measurements, the available pressure differences between supply volume and reactor volume are varied from 1 bar to 4 bar, then effects of the pressure interval (pressure difference) during each step of the absorption/desorption PCI measurement on the hydrogen storage capacity, equilibrium pressure, plateau slope, metal hydride bed temperature and hysteresis are studied. All of these properties showed a significant variation with pressure intervals. Later, to study the effect on thermodynamic properties, van't Hoff plots are constructed for wide temperature range and reaction enthalpies are calculated for different temperature points. The effect of the temperature range on the enthalpy of formation is observed to be dependent on the experimental temperature range.